2020
DOI: 10.1002/bit.27620
|View full text |Cite
|
Sign up to set email alerts
|

A review of manufacturing capabilities of cell spheroid generation technologies and future development

Abstract: Spheroid culture provides cells with a three‐dimensional environment that can better mimic physiological conditions compared to monolayer culture. Technologies involved in the generation of cell spheroids are continuously being innovated to produce spheroids with enhanced properties. In this paper, we review the manufacturing capabilities of current cell spheroid generation technologies. We propose that spheroid generation technologies should enable tight and robust process controls to produce spheroids of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 99 publications
0
32
0
1
Order By: Relevance
“…Microfluidic large-scale integration (mLSI) enables the automation of cell culture processes in a highly parallel manner, with precise spatiotemporal control of the cellular microenvironment. [1][2][3] mLSI platforms have been utilized for various cell culture processes, including high-throughput single-cell analysis, 4 standardized stem cell differentiation, 5 protein signaling analysis, 6 conditional transcriptomics, 7 and cell-to-cell interaction analysis. 8 To date, the majority of mLSI applications utilize traditional two-dimensional (2D) monolayer cell cultures, which provide robust, cost-effective, and repeatable access to cell screening assays.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic large-scale integration (mLSI) enables the automation of cell culture processes in a highly parallel manner, with precise spatiotemporal control of the cellular microenvironment. [1][2][3] mLSI platforms have been utilized for various cell culture processes, including high-throughput single-cell analysis, 4 standardized stem cell differentiation, 5 protein signaling analysis, 6 conditional transcriptomics, 7 and cell-to-cell interaction analysis. 8 To date, the majority of mLSI applications utilize traditional two-dimensional (2D) monolayer cell cultures, which provide robust, cost-effective, and repeatable access to cell screening assays.…”
Section: Introductionmentioning
confidence: 99%
“…Spheroids can be derived from either established cell lines or primary isolated tumor cells [ 35 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ]. Usually, spheroids are obtained culturing tumor cells in ultra-low adherent plasticware or by hanging drop methods, forcing tumor cells to aggregate and generate tumor sphere in static or microfluidic systems [ 15 , 16 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 ].…”
Section: Tumor Cell Spheroids As a 3d Model To Study Tumor Cell Biology And Tumor-natural Killer Cross-talkmentioning
confidence: 99%
“…Cells are aggregated into a spheroid and cultured in suspension. Various spheroid fabrication methods such as hanging drop, non-adherent culture plate, gel embedding, magnetic levitation, and spinner culture have been reported ( 11 , 14 - 16 ). It has been demonstrated that cell spheroids exhibit improved cellular functions in vitro as compared to a monolayer culture ( 17 ).…”
Section: Introductionmentioning
confidence: 99%